Decentralization and the Fulfilments of Children's Rights: Challenges and Opportunities for Local Government in Indonesia - Hariyanto Hariyanto; Ahmad Rezy Meidina; Mabarroh Azizah (Lex Scientia Law Review, 2024)
The commitment of local governments to protect children in areas such as education, violence, and discrimination is illustrated by Banyumas Regency's Local Regulation Number 1 of 2021, which addresses child protection. However, several challenges persist in its implementation. This study investigates the role of decentralization through local regulations related to child protection, employing normative legal research methods that include a regulatory approach, conceptual analysis, and case studies. The findings indicate that Banyumas Local Regulation No. 1 of 2021 establishes a strong legal framework that significantly protects children from discrimination, violence, and educational inequities. Nevertheless, implementation faces numerous obstacles, including inadequate inter-agency coordination, insufficient infrastructure, limited funding, and a lack of public awareness regarding the importance of protecting children's rights. This research proposes increasing funding allocations through the Regional Budget and recommends creating a collaborative forum that includes local governments, relevant agencies, schools, community organizations, and law enforcement to enhance policy coordination and action. Furthermore, the government is urged to improve community outreach regarding decentralized regulations that protect children. Ultimately, it is crucial to evaluate and refine existing policies to ensure the protection of minors' rights and to provide legal security and certainty.